Birth weight for gestational age and later cardiovascular health: a comparison between longitudinal Finnish and indigenous Australian cohorts - Sjöholm Paula; Pahkala Katja; Davison Belinda; Niinikoski Harri; Raitakari Olli; Juonala Markus; Singh Gurmeet R (TAYLOR & FRANCIS LTD, 2022)
Introduction: Small or large birth weight for gestational age has been linked with later cardiovascular disease risk. However, cardiovascular risk markers from childhood to adulthood according to birth weight in diverse longitudinal settings globally have not been extensively studied.
Objectives: To examine the relationship between birth weight and cardiovascular risk profile from childhood until young adulthood in two geographically and socioeconomically distinct cohorts.
Methods: Data were derived from two longitudinal birth cohort studies; one from southern Finland (Special Turku Coronary Risk Factor Intervention Project, STRIP) and one from northern Australia comprising Indigenous Australians (Aboriginal Birth Cohort, ABC). The sample included 747 Finnish participants and 541 Indigenous Australians with data on birth weight, gestational age and cardiovascular risk factors (body mass index [BMI]), waist-to-height ratio [WHtR], lipid profile, blood pressure) collected at ages 11, 18 and 25 or 26 years. Carotid intima-media thickness (cIMT) was assessed at age 18 or 19 years. Participants were categorised according to birth weight for gestational age (small [SGA], appropriate [AGA] or large [LGA]). Associations between birth weight category and cardiovascular risk markers were studied using a repeated measures ANOVA.
Results: Higher birth weight category was associated with higher BMI later in life in both cohorts (p=.003 for STRIP and p<.0001 for ABC). In the ABC, higher birth weight category was also associated with higher WHtR (p=.004). In the ABC, SGA participants had lower systolic and diastolic blood pressure than AGA participants (p=.028 for systolic, p=.027 for diastolic) and lower systolic blood pressure than LGA participants (p=.046) at age 25. In the STRIP cohort, SGA participants had lower cIMT than LGA participants (p=.024).
Conclusions: Birth weight can predict future cardiovascular risk profile in diverse populations. Thus, it needs to be included in targeted public health interventions for tackling the obesity pandemic and improving cardiovascular health worldwide.Key messagesThe strongest association between birth weight and later cardiovascular risk profile was manifested as differences in body mass index in two culturally and geographically distinct cohorts.Foetal growth is a determinant for later cardiovascular health in diverse populations, indicating a need to focus on maternal and foetal health to improve cardiovascular health worldwide.